O ensino de segundo grau em O Estado de S.Paulo (1972-1977) - Ribeiro, Leisa Alves (2007)
This master dissertation presents the results of a research whose purpose was to organize and analyse the articles and editorials about Secondary Education published in the newspaper O Estado de S. Paulo (OESP) from 1972 to 1977, when the educational reform 5692 was implemented. We aimed to examine how this newspaper, which always had Education as one of its principal themes in its pages, printed the reform and reacted to the government s reform and its implementation. Due to the military dictatorship, the approaches of the articles and editorials published in OESP vary between a soft and hard tone, a tendency found in the Brazilian media. When the political program distensão - a gradual relaxation of the authoritarian rule - takes place in the country, the editorials and articles, that before only showed the difficulties to implement the reform in the Brazilian States, started to criticize openly the government and to show that the reform was a failure. At this period, OESP interviewed people from several social fields to speak about the Secondary Educational System. Lack of educational facilities and financial aid were pointed as the reason of the failure of the reform. Besides that, the newspaper OESP shows that its ideas about Secondary Education are opposed to the reform proposed by the government. The former is for academic studies whereas the latter for a technical education